A novel guide for minimally invasive genioplasty - Macedo, Diogo de Vasconcelos [UNESP]; Monnazzi, Marcelo Silva [UNESP]; de Almeida, Matheus Spinella; Claus, Jonathas Daniel Paggi (Springer Nature, 2022)
Mentoplasty or genioplasty is a simple procedure to enhance facial aesthetics. While usually considered simple, it might present certain difficulties during execution, especially when a minimally invasive approach is preferred. Drilling and cutting guides are a valuable tool to overcome such challenges but usually require larger incision and dissection to allow adequate positioning and bone rigid fixation. In this article, we describe a novel guide design that permits adequate bone repositioning while preserving minimally invasive protocols.
Keywords: Aesthetics; Chin; Genioplasty; Orthognathic surgery